Flesh : a novel - Szalay, David (Scribner, 2025)
From Booker Prize-shortlisted author David Szalay, comes a propulsive, hypnotic novel about a man who is unravelled by a series of events beyond his grasp. Fifteen-year-old Istvan lives with his mother in a quiet apartment complex in Hungary. New to the town and shy, he is unfamiliar with the social rituals at school and soon becomes isolated, with his neighbour -- a married woman close to his mother's age -- as his only companion. These encounters shift into a clandestine relationship that Istvan himself can barely understand, and his life soon spirals out of control. As the years pass, he is carried gradually upwards on the currents of the twenty-first century's tides of money and power, moving from the army to the company of London's super-rich, with his own competing impulses for love, intimacy, status and wealth winning him unimaginable riches, until they threaten to undo him completely. Spare and penetrating, Flesh is the finest novel yet by a master of realism, asking profound questions about what drives a life: what makes it worth living, and what breaks it.